2016
DOI: 10.5101/nbe.v8i4.p306-314
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Genotoxicity of Gold Nanorods in Mouse Bone Marrow Compared with Cyclophosphamide

Abstract: Gold nanorods (GNRs) are now under extensive investigation for biomedical applications. The in vivo genotoxic profile GNRs are not elucidated yet, therefore we investigated it in comparison with one of the most effective chemotherapeutic agents, cyclophosphamide (CP), in a mice model. PEGylatedGNRs (50 nm) were injected to Balb/C mice triple times, while CP-treated mice were treated once and the bone marrow cells (BMCs) were collected after 21 days. Chromosome aberrations, mitotic index, sister chromatid excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As far as we know, this is the first report concerning AuNP formation using a guanine moiety without any additional reducing reagents or physical stresses. To date, broad technological strategies have been studied toward developing AuNPs in the fields of optical sensing and imaging, drug delivery, cancer therapy, and so on. , To exploit the homologous shape and size, dispersibility, and easy production of the AuNPs generated for the medical and pharmaceutical fields, we also need to develop methods to recover AuNPs from the carrier and modify their surfaces to provide affinitive and reactive properties to AuNPs and study their toxicity to target animal cells and other essential basic issues such as the stability of AuNPs in various salt solutions that are used routinely for biological applications.…”
Section: Results and Discusionmentioning
confidence: 99%
“…As far as we know, this is the first report concerning AuNP formation using a guanine moiety without any additional reducing reagents or physical stresses. To date, broad technological strategies have been studied toward developing AuNPs in the fields of optical sensing and imaging, drug delivery, cancer therapy, and so on. , To exploit the homologous shape and size, dispersibility, and easy production of the AuNPs generated for the medical and pharmaceutical fields, we also need to develop methods to recover AuNPs from the carrier and modify their surfaces to provide affinitive and reactive properties to AuNPs and study their toxicity to target animal cells and other essential basic issues such as the stability of AuNPs in various salt solutions that are used routinely for biological applications.…”
Section: Results and Discusionmentioning
confidence: 99%
“…The toxicity of gold nanoparticles in vivo is directly related to their size, shape [21][22], surface coating, exposure dose and administration routes [23]. Developing favourable nanomaterials with efficient renal clearance is extremely important to their in-vivo biomedical applications [24,25]. It has been demonstrated that the size plays a dominant role [26].…”
Section: Introductionmentioning
confidence: 99%